Analisis Analisis Metode Pembelajaran dalam Hadist: Implementasi dan Relevansinya dalam Pendidikan Modern: Analisis Metode Pembelajaran dalam Hadist: Implementasi dan Relevansinya dalam Pendidikan Modern - Hariyanto, Wawan (Jurnal Staika: Jurnal Penelitian dan Pendidikan, 2024)
This study presents an analysis of learning methods found in hadith and their relevance in the context of modern education. Using a qualitative approach and content analysis, this study identifies four main methods found in the hadith: lecture, discussion, question and answer, and exemplification. The research findings show that these methods reflect pedagogical principles that can be effectively integrated in modern education. Discussion involves the exchange of ideas and critical thinking between teachers and students, in line with the collaborative learning approach valued in contemporary education. The question and answer method, used extensively by the Prophet Muhammad, encourages students' active participation and deepens their understanding of the material being studied. Meanwhile, practical demonstrations help students understand abstract concepts through hands-on experience. The results of this study have important implications for the development of Islamic values-based pedagogy in modern education. The integration of learning methods from hadith can enrich teaching practices by combining Islamic spiritual and ethical values with contemporary educational approaches that emphasize interactivity and active student participation.